Competency-Based Teacher Education A Potpourri of Perspectives, ATE Bulletin No. 38 - Association of Teacher Educators, Reston, VA.; Ishler, Richard E.; Association of Teacher Educators, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This document contains nine essays which provide guidelines and directions for implementing competency-based teacher education (CBTE) programs. Selections include the following: (a) "Characteristics of Competency-based Teacher Education Programs;" (b) "The Development of a Comprehensive Competency-Based Teacher Education Program: A Model for Change;" (c) "Process to Product: A Competency-Based Teacher Education Program in Student Teaching;" (d) "Initiating a Performance-Based Teacher Education Conversion on a Shoestring;" (e) "Competency-Based Teacher Education in Small Colleges and Rural Areas;" (f) "Performance Contracting for Student Teachers;" (g) "Evaluation of Teacher Competence Based on Pupil Behaviors;" (h) "The Relationship Between Education Accreditation Criteria and the Competency Approach;" and (i) "Current Responses to Competency-Based Teacher Education:" Selected references are included at the end of each essay. (JS)
Availability: Association of Teacher Educators, Suite 1201, 1701 K Street, N. W., Washington, D. C. 20006 (Stock No. 861-27410, $3.50).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Competency Based Teacher Education; Higher Education; Nontraditional Education; Performance Contracts; Program Budgeting; Program Development; Rural Education; Small Colleges; Teacher Certification; Teacher Education; Teacher Evaluation; Books